Sleep Disturbances among Older Adults in the United States, 2002–2012: Nationwide Inpatient Rates, Predictors, and Outcomes - Gamaldo, Alyssa A.; Beydoun, May A.; Beydoun, Hind A.; Liang, Hailun; Salas, Rachel E.; Zonderman, Alan B.; Gamaldo, Charlene E.; Eid, Shaker M. (Frontiers in Aging Neuroscience, 2016)
OBJECTIVE/BACKGROUND: We examined the rates, predictors, and outcomes (mortality risk (MR), length of stay (LOS) and total charges (TC)) of sleep disturbances in older hospitalized patients. PATIENTS/METHODS: Using the U.S. Nationwide Inpatient Sample database (2002-2012), older patients (≥60y) were selected and rates of insomnia, obstructive sleep apnea (OSA) and other sleep disturbances (OSD) were estimated using ICD-9CM. TC, adjusted for inflation, was of primary interest, while MR and LOS were secondary outcomes. Multivariable regression analyses were conducted. RESULTS: Of 35,258,031 older adults, 263,865 (0.75%) had insomnia, 750,851 (2.13%) OSA and 21,814 (0.06%) OSD. Insomnia rates increased significantly (0.27% in 2002 to 1.29 in 2012, P-trend<0.001), with a similar trend observed for OSA (1.47 in 2006 to 5.01 in 2012, P-trend<0.001). TC (2012 $) for insomnia-related hospital admission increased over time from $22,250 in 2002 to $31,527 in 2012, and increased similarly for OSA and OSD; while LOS and MR both decreased. Women with any sleep disturbance had lower MR and TC than men, while Whites had consistently higher odds of insomnia, OSA, and OSD than older Blacks and Hispanics. Co-morbidities such as depression, cardiovascular risk factors, and neurological disorders steadily increased over time in patients with sleep disturbances. CONCLUSION: TC increased over time in patients with sleep disturbances while LOS and MR decreased. Further research should focus on identifying the mechanisms that explain the association between increasing sleep disturbance rates and expenditures within hospital settings and the potential hospital expenditures of unrecognized sleep disturbances in the elderly.